Tindak Tutur Ilokusi Asertif dalam Pernyataan Klarifikasi Figur Publik Pelaku Pelecehan Seksual di Media Sosial - Endah Sawitri; Eqy Wahyu Ramadhani; Putri Rahma Nurjannah; Rahma Delviani; Sevia Amartha Putri; Yasmina Zalfa; Asep Purwo Yudi Utomo; Nancy Angelia Purba (Pusat riset dan Inovasi Nasional, 2026)
Public figure clarifications on social media have become a complex space for truth contestation in digital society. This research is motivated by the strategic use of linguistic devices by public figures to restore their image and construct a narrative of truth following digital conflicts. The purpose of this study is to identify and describe the various functions of assertive illocutionary speech acts used by Mohan Hazian, Panji Sukma, and Roby Tremonti in their clarification videos. The method used is descriptive qualitative with a pragmatic approach. Data were collected using listening and note-taking techniques, then analyzed based on Searle's speech act taxonomy. The results of the study revealed 45 data points of assertive speech acts divided into eight functions, namely stating, denying, reporting, assessing, emphasizing, admitting, claiming, and complaining. The functions of stating and denying are the most dominant as instruments of self-defense. These findings prove that speakers combine logical facts with emotional aspects to regain public trust. The benefit of this research is to provide a theoretical contribution to the development of pragmatic studies regarding crisis communication strategies in digital media and to serve as a guide for the public to be more critical in dissecting the intent behind public figure clarifications.